2019
DOI: 10.15244/pjoes/91078
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Nano Silica Nanoparticles from Barley Grain Waste: Effect of Temperature on Mechanical Properties

Abstract: In this investigation we report the synthesis of nano silica (NS) nanoparticles from barley grass waste-an environmental burden-using varying temperatures during preparation. The temperatures used during the investigation were 400, 500, 600, and 700ºC, and we studied its effects on the mechanical properties of the NS nanoparticles for use in environmentally friendly applications. Furthermore, the NS nanoparticles resulting from high temperature synthesis were characterized using various characterization method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 18 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…The bending vibration at 3452.34 and 1633.59 cm -1 were due to the H-O-H, stretching of different hydroxyl groups of adsorbed water molecules on the silica surface which reflected the high purity of precipitated Nanosilica and give adsorption characteristic of particles (6). The band peaks between 4000-400 cm -1 are the main indicator of the silica material, which represents the successful production of silica nanoparticles from rice husk (19).…”
Section: Figure 6 Afm Analysis A) Particles Size Distribution B) Scamentioning
confidence: 99%
“…The bending vibration at 3452.34 and 1633.59 cm -1 were due to the H-O-H, stretching of different hydroxyl groups of adsorbed water molecules on the silica surface which reflected the high purity of precipitated Nanosilica and give adsorption characteristic of particles (6). The band peaks between 4000-400 cm -1 are the main indicator of the silica material, which represents the successful production of silica nanoparticles from rice husk (19).…”
Section: Figure 6 Afm Analysis A) Particles Size Distribution B) Scamentioning
confidence: 99%
“…The highest peak of the nano-silica particle was observed at 2θ = 24.8 • . According to the XRD results, it is valid to say that the method of synthesis of nano-silica from barley resulted in particles with significantly low impurities [9,16]. Lastly, it can be seen from the XRD result that there were no substantial changes observed in case of the peaks for magnetic nano silica, as shown in Figure 4a-A, although a new peak was identified at 2θ = 20-30 • , which indicates the presence of amorphous silica.…”
Section: Characterization Results Of Magnetic Silica Nanoparticlesmentioning
confidence: 95%
“…The synthesis procedure for producing nano-silica, as shown in Figure 1, is also described elsewhere by Akhayere et.al. [9]. The resulting nano silica powder was used for the preparation of nano silica solution.…”
Section: Synthesis Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Akhayere et al [12] reported the synthesis of nanosilica from barley grass waste-an environmental burden-using varying temperatures during preparation. The temperatures used during the investigation were 400, 500, 600, and 700 • C, studying its effects on the mechanical properties of the nanosilica for use in environmentally friendly applications.…”
Section: Introductionmentioning
confidence: 99%